PIETY COMMODIFICATION OF NIQABIS IN SOCIAL MEDIA INSTAGRAM - Qurrota A'yunin; Endah Triastuti (EGALITA, 2022)
This study explains how the term of piety which is shown by well-known niqabis women on a social media like Instagram that has been negotiated and commodified for a certain reason. By using theoretical concept concerning on Commodification of Piety, which means labelling the name of Islam (kind of a new piety) to explain commodity (Shirazi, 2016), this study argues that by using Instagram, niqabis women who have an online Muslim clothing brand has modified the values of piety on women’s body in Islamic context. A qualitative approach of feminist paradigm was used to see the various digital data of a caption and photo in their Instagram posts. The result of this study shows that niqabis exploit the values of piety in the form of “hijrah” and “syar’i clothing” categorization to build an Islamic brand that unconsciously contains Muslim women body knowledge propaganda. This study concludes that there is a commodification process on the values that constructed on Instagram. That process is not only involving niqab and the piety, but also the commodity of women body to praise the Muslim clothing product sale.